Strategi Membangun Budaya Akademik Mahasiswa - Supriyanto Supriyanto (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2021)
Abstract: This study aims to describe strategies in developing the academic culture of FIP Students along with its supporting and inhibiting factors. The research method used is case study. The Research subjects include faculty and department leaders, lecturers, sub-academic staff, and students. Data collection is using interviews, observation, and documentation. Data were analyzed descriptively qualitative. The result of the research shows: 1) the strategy on improving the academic culture of the students is to budget funds for scientific activities, collaborating student activities with academic activities, provide motivation and empowerment to students, involve students in research activities and community service, conduct training on scientific writing programs and plagiarism prevention, engaging students in various scientific competition events, facilitating the formation of a student scientific community, developing academic networks with foreign universities through student exchange, intensifying academic awareness; 2) supporting factors on improving student academic culture is the amount of financial and non-financial support from the leadership and availability of supporting resources, while the inhibiting factors are the low motivation of students to follow scientific activities and too many non-scientific activities in the work of student organizations. Abstrak: Penelitian ini bertujuan untuk mendeskripsikan strategi dalam meningkatkan budaya akademik Mahasiswa FIP beserta faktor pendukung dan penghambatnya. Metode penelitian yang digunakan adalah studi kasus. Subjek penelitian meliputi pimpinan fakultas dan jurusan, dosen, staf sub.bagian akademik, dan mahasiswa. Pengumpulan data menggunakan wawancara, observasi, dan dokumentasi. Data dianalisis secara deskriptif kualitatif. Hasil penelitian menunjukkan: 1) strategi dalam meningkatkan budaya akademik mahasiswa adalah menganggarkan dana untuk kegiatan ilmiah, mensinergikan kegiatan kemahasiswaan dengan kegiatan akademik, memberikan motivasi dan penguatan kepada mahasiswa, melibatkan mahasiswa dalam kegiatan penelitian dan pengabdian manyarakat, mengadakan pelatihan kepenulisan ilmiah dan pencegahan plagiasi, mengikutsertakan mahasiwa dalam berbagai kegiatan kompetisi ilmiah, memfasilitasi pembentukan komunitas ilmiah mahasiswa, membangun jejaring akademik dengan perguruan tinggi luar negeri melalui student exchange, mengintensifkan kepenasehatan akademik; 2) faktor pendukung dalam meningkatkan budaya akademik mahasiswa adalah besarnya dukungan finansial dan non finansial dari pimpinan dan tersedianya sumberdaya pendukung, sementara faktor penghambat adalah rendahnya motivasi mahasiswa dalam mengikuti kegiatan ilmiah dan terlalu banyak kegiatan non ilmiah dalam program kerja organisasi mahasiswa.